Tuning the Synthetic Parameters to Obtain Smart C‐N Co‐Doped Titania Photocatalysts for NOx Abatement. Issue 2 (13th January 2017) - Olivo, A.; Ghedini, E.; Pinna, F.; Marchese, D.; Signoretto, M.; Cruciani, G.; Manzoli, M.
Abstract: Global society is constantly seeking for sustainable and effective processes to fight environmental pollution. The abatement of NOx, a class of hazardous contaminants, can be performed by means of photocatalytic oxidation using titania‐based photocatalysts. Non‐metal doping is highly desirable for an efficient exploitation of solar light. The co‐presence of nitrogen and carbon represents an appealing possibility though their introduction generally requires post‐synthesis treatments. Otherwise, in this work carbon and nitrogen have been introduced in titania photocatalysts simultaneously by a one‐pot synthetic approach using a natural and sustainable source of dopants, namely chitosan. Several synthetic parameters have been changed in order to evaluate their effect on the physicochemical properties of the final materials and to establish structure‐activity relationship as for the photocatalytic performances in NOx oxidation under visible light irradiation. Abstract : Chitosan, a sustainable and environmentally friendly natural polymer, is a promising source to introduce C and N into TiO2 based materials through a time and energy saving procedure. This method is indeed effective to this purposes leading to a tremendous increase in photocatalytic activity in NO oxidation.